O papel do coordenador pedagógico no processo formativo dos professores do ciclo de alfabetização: o Pacto Nacional pela Alfabetização na Idade Certa - PNAIC - Santos, Cintia Anselmo dos (2015)
This survey was conducted in order to deepen studies that support the work of the pedagogical coordinator for the guidance of the work of teachers of literacy cycle, based on the following question: As the coordinators, who work with teachers of literacy cycle, can reframe forming their actions, to integrate participants PNAIC teachers in mathematics literacy axis, to qualify the work at schools? Its overall goal: To prepare recommendations to the coordinators to help them promote (or reframe) in-service training with teachers of literacy cycle, supported on the knowledge and skills built by teachers in training processes carried out in PNAIC to qualifying student learning in the classroom. And for specific objectives: Describe the PNAIC, analyzing their overall objectives, its constitution, content addressed and assumptions; Analyze the teacher's learning characteristics, in continuing training processes; List the duties of the pedagogical coordinator, considering the possibilities of conducting continuing education processes supported in the knowledge of teachers, as a way of reflection and sharing to improve teaching practices The research was developed in the form of qualitative research, based on desk research and literature, and the experiences of the researcher. The recommendations made, although they represent a first effort to systematize the question, can represent reflection element and any change in the practice of educational coordinators and teachers